The Influence of Culture and Lifestyle on Purchasing Decisions of Women's Clothing at Matahari Department Store, Palopo City - Rudianto Rudianto (International Journal of Management Progress, 2021)
This study aims to determine, the influence of culture and lifestyle on purchasing decisions for women's clothing at Matahari Department Store Palopo City, cultural influences on purchasing decisions for women's clothing at Matahari Department Store Palopo City, and the influence of lifestyle on purchasing decisions for women's clothing at Matahari Department Store. Palopo City. The method used is multiple regression analysis method with a sample size of 30 respondents. The focus of the research determined by the researcher was only on women's clothing products, so the researcher only chose female respondents. The characteristics of the respondents analyzed in this study were based on age and occupation. The research data was obtained by distributing questionnaires to respondents. The results showed that the t value of cultural variables was 3.446 with a significant level of 0.002. Because 3.446 > 2.051 and 0.002 < 0.05, the hypothesis is accepted. This shows that the cultural variable (X1) has a positive and significant effect on purchasing decisions. While the t value of the lifestyle variable (X2) is 2.537 with a significant level of 0.017. Because 2.537 > 2.051 and 0.017 < 0.05, the hypothesis is accepted. This shows that lifestyle variables have a positive and significant effect on purchasing decisions. The simultaneous test results show that the cultural variables (X1) and lifestyle (X2) together have a positive effect on purchasing decisions (Y) as evidenced by the calculated F value of 17.055 with a significant level of 0.000, where F count > F table (17.055 > 3.35) with a significance level less than 0.05 (0.000 < 0.05).